The Impact of the Sarbanes-Oxley Act on the Cost of Going Public - Christoph Kaserer; Alfred Mettler; Stefan Obernberger (BuR - Business Research, 2011)
This paper examines the impact of the Sarbanes-Oxley Act (SOX), a legal framework intended to increase transparency and accountability of listed companies, on the cost of going public in the US. We expect SOX to increase the direct cost of going public, but decrease the underpricing because of reduced asymmetric information. Our main results corroborate these hypotheses. First, we find an increase in the cost of going public of 90 bp of gross proceeds. Second, we record a reduction in underpricing of 6 pp, which is related to a reduced offer price adjustment. This supports our hypothesis that SOX represents a mechanism to reduce asymmetric information.
urn:nbn:de:0009-20-32074
Keywords: 650; asymmetric information; auditing and legal fees; bookbuilding; IPO; flotation cost; going public; partial adjustment phenomenon; propensity score matching; selection bias; SOX; underpricing; underwriting fees; Internes Kontrollsystem; Börsengang; Kostenmanagement; Asymmetrische Information; USA